2000
DOI: 10.1073/pnas.97.2.865
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of BETA2/NeuroD leads to malformation of the dentate gyrus and epilepsy

Abstract: BETA2/NeuroD is a homologue of the Drosophila atonal gene that is widely expressed during development in the mammalian brain and pancreas. Although studies in Xenopus suggest that BETA2/NeuroD is involved in cellular differentiation, its function in the mammalian nervous system is unclear. Here we show that mutant mice homozygous for a deletion at the BETA2/NeuroD locus fail to develop a granule cell lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
270
2
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(282 citation statements)
references
References 35 publications
9
270
2
1
Order By: Relevance
“…To identify potential targets of Wnt signaling within the hippocampal niche, we focused on genes expressed in the adult DG. Prox1 is a prospero-related homeodomain transcription factor, which is highly expressed in DG granule cells (10,15,16). Prox1 has previously been shown to be important for lens development, lymphangiogenesis, differentiation of certain spinal cord interneurons, and, very recently, in hippocampal granule cell genesis (17)(18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify potential targets of Wnt signaling within the hippocampal niche, we focused on genes expressed in the adult DG. Prox1 is a prospero-related homeodomain transcription factor, which is highly expressed in DG granule cells (10,15,16). Prox1 has previously been shown to be important for lens development, lymphangiogenesis, differentiation of certain spinal cord interneurons, and, very recently, in hippocampal granule cell genesis (17)(18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
“…There, β-catenin acts as a transcriptional coactivator of TCF/LEF transcription factors, resulting in the expression of Wnt target genes. Recently, it has been shown that NeuroD1, a basic helix-loop-helix transcription factor required for granule cell genesis in the embryonic and adult DG, is regulated by β-catenin-dependent signaling (9)(10)(11)(12). However, NeuroD1 is not only important for hippocampal neurogenesis but is also involved in the generation of SVZ-derived olfactory neurons (11,13,14).…”
mentioning
confidence: 99%
“…Given that NeuroD1 deficiency in mice is generally associated with perinatal lethality (14,15,21), we used a strategy based on RNAi in concert with postnatal in vivo electroporation to knock down NeuroD1 in the olfactory bulb neurogenic system. For validation, three different NeuroD1 specific shRNA vectors were cotransfected with a NeuroD1 expression construct into COS-7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…To do so we isolated neuronal precursors and differentiated interneurons from the periglomerular lineage of the OB and compared their gene expression by microarray. We established that the expression of NeuroD1, a bHLH transcription factor that has been implicated in neuronal differentiation in several experimental systems (13)(14)(15)(16)(17), coincides with the passage from neuronal precursor to mature interneurons. Functionally, we show that premature expression of NeuroD1 in vitro and in vivo induced highly efficiently the differentiation of forebrain progenitors.…”
mentioning
confidence: 99%
“…NeuroD1 knockout mice display a malformation of the dentate gyrus, one of the principal structures of the hippocampus, and exhibit spontaneous limbic seizures. 23 ATF2 is a leucine zipper transcription factor, which binds to cAMP-response elements (CREs), forming homodimers or heterodimers with c-jun to stimulate CRE-dependent transcription. 24 The protein also has intrinsic histone acetyltransferase activity, which is modulated by phosphorylation, and has been proposed to activate transcription by direct effects on chromatin components.…”
mentioning
confidence: 99%